MR imaging–and MR spectroscopy–revealed Changes in Meningiomas for which Embolization was Performed without Subsequent Surgery - Bendszus, Martin; Martin-Schrader, Ignatio; Warmuth-Metz, Monika; Hofmann, Erich; Solymosi, Laszlo (American Journal of Neuroradiology, 2000)
Summary: We describe our experience with follow-up MR imaging and MR spectroscopy in two patients after embolization of meningiomas without subsequent surgery. In both patients there was a marked reduction in tumor size and a decrease in contrast enhancement associated with spectroscopic signs of fatty degeneration. We did not observe regrowth; however, in one patient with incomplete angiographic devascularization, residual vital tumor tissue was seen at follow-up examinations.